#Yoentrenoencasa, an initiative to keep moving: Analysis of content published on Instagram - López-López, Claudia; Saavedra-García, Miguel Ángel; López-Villar, Cristina (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The use of social media has been consolidated in the field of physical activity and sports. The arrival of the Covid-19 pandemic promoted these tools as an online resource for exercise. During confinement, institutions and content creators promoted initiatives through these platforms to continue moving from home, such as the creation of the hashtag #Yoentrenoencasa. This study aimed to discover the main characteristics of this community through a content analysis of 600 posts shared on Instagram during confinement. The results showed that content related to physical activity with the intention of inspiring the audience predominated, in which women mainly appeared. The weight of publications focused on promoting online training services and creating physical exercise routines could also be seen. In this content, certain sexist differences were uncovered, since women were represented in a more passive manner than men, who were portrayed in competitive or professional situations.